Chronic non-communicable diseases: Hainan prospective cohort study - Ling Wu; Fan Zhang; Yumei Liu; Xingbo Gu; Liuting Lin; Chanjuan Zhao; Limin He; Guotian Lin; Yingzi Lin (BMJ Open)
Purpose The Hainan Cohort was established to investigate the incidence, morbidity and mortality of non-communicable diseases and their risk factors in the community population.Participants The baseline investigation of the Hainan Cohort study was initiated in five main areas of Hainan, China, from June 2018 to October 2020. A multistage cluster random-sampling method was used to obtain samples from the general population. Baseline assessments included a questionnaire survey, physical examination, blood and urine sample collection, and laboratory measurements, and outdoor environmental data were obtained.Findings to data A total of 14 443 participants aged 35–74 years were recruited at baseline, with a participation rate of 90.1%. The mean age of the participants was 48.8 years; 51.8% were men, and 83.7% had a secondary school or higher education. The crude prevalence of diabetes, coronary heart disease, stroke, hypertension, hyperuricaemia, chronic bronchitis, pulmonary tuberculosis, asthma, cancer, chronic hepatitis and metabolic syndrome were 8.6%, 9.2%, 2.0%, 37.1%, 7.1%, 2.3%, 1.4%, 2.1%, 4.1%, 2.2% and 14.5%, respectively.Future plans The Hainan Cohort is a dynamic cohort with no end date. All participants will be monitored annually for cause-specific mortality and morbidity until death. Long-term follow-up will be conducted every 5 years. The baseline population is considered to expand in the next wave of follow-up, depending on the availability of funding support.